Simulation of nonlinear systems subject to modulated chirp signals. Issue 4 (6th July 2015) - Condon, M.; Iserles, A.
Abstract : Purpose: – The purpose of this paper is to apply a novel technique for the simulation of nonlinear systems subject to modulated chirp signals. Design/methodology/approach: – The simulation technique is first described and its salient features are presented. Two examples are given to confirm the merits of the method. Findings: – The results indicate that the method is appropriate for simulating nonlinear systems subject to modulated chirp signals. In particular, the efficiency and accuracy of the method is seen to improve as the chirp frequency increases. In addition, error bounds are given for the method. Originality/value: – Chirp signals are employed in several important applications such as representing biological signals and in spread spectrum communications. Analysis of systems involving such signals requires accurate, appropriate and effective simulation techniques.